Verapamil blocks HERG channel by the helix residue Y652 and F656 in the S6 transmembrane domain - Duan Jing-jing; Ma Ji-hua; Zhang Pei-hua; Wang Xian-pei; Zou An-rou; Tu Dan-na (Acta Pharmacologica Sinica, 2016)
Aim: The objectives of this study were to investigate the inhibitory action of verapamil on wild-type(WT) and mutation HERG K+ channel current (IHERG), and to determine whether mutations in the S6 region are important for the inhibition of IHERG by verapamil. Methods: HERG channels (WT, Y652A, and F656A) were expressed in oocytes of Xenopus laevis and studied using the 2-electrode voltage-clamp technique. Results: WT HERG is blocked in a concentration-dependent manner by verapamil (half-maximal inhibition concentration [IC50]=5.1 μmol/L), and the steady state activation and inactivation parameters are shifted to more negative values. However, mutation to Ala of Y652 and F656 located on the S6 domain produced 16-fold and 20-fold increases in IC50 for IHERG blockade, respectively. Simultaneously, the steady state activation and inactivation parameters for Y652A are also shifted to more negative values in the presence of the blockers. Conclusion: Verapamil preferentially binds to and blocks open HERG channels. Tyr-652 and Phe-656, 2 aromatic amino-acid residues in the inner (S6) helix, are critical in the verapamil-binding site.